2019
DOI: 10.1002/mar.21296
|View full text |Cite
|
Sign up to set email alerts
|

When open‐mindedness lowers product evaluations: Influencers to consumers’ response to religious cues in advertising

Abstract: Prior research has examined response to Christian religious cues used in secular marketing messages but has inadequately explored the underlying reasons for such response as well as why religious cues may negatively influence product evaluations. These limitations are addressed in this research work through three studies utilizing religious cues. In Studies 1a and 1b, ads with a Christian or Muslim religious cue (no religious cue) were found to produce lower (higher) product evaluations. Studies 2-3 then exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Generally, higher religiosity consumers across religious affiliations follow set traditions of their faith dictated centuries ago (Schmidt et al, 2014). More generally, prior research has shown that religiosity has a variety of influences on consumer behavior (Choudhury, 2014; LaBarbera & Gurhan, 1997; Minton, 2020; Muhamad & Mizerski, 2013; Youn et al, 2000).…”
Section: Values Religiosity and Aimentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, higher religiosity consumers across religious affiliations follow set traditions of their faith dictated centuries ago (Schmidt et al, 2014). More generally, prior research has shown that religiosity has a variety of influences on consumer behavior (Choudhury, 2014; LaBarbera & Gurhan, 1997; Minton, 2020; Muhamad & Mizerski, 2013; Youn et al, 2000).…”
Section: Values Religiosity and Aimentioning
confidence: 99%
“…A growing body of prior research has suggested that religiosity serves as an important basis for market segmentation, where social media more easily allows marketers to target individuals that self‐identify as higher in religiosity (see Agarwala et al, 2019; Mathras et al, 2016, for reviews). Other research shows that simple religious‐based cues can be used in marketing communications to prime the broad construct of religion, thereby heightening religiosity (Dotson & Hyatt, 2000; Minton, 2020), which can then be partnered with messages to address specific concerns regarding AI in marketing, such as trust. For example, using the language “creation of flavor” can be enough to prime religion (Minton, 2015), which could then be partnered with messages and in chatbot services/descriptions to communicate how long a company has been in operation, the ethics of their employees that are managing AI use in marketing, or quality control measures in place to handle trust (Morhart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the association of perceived religious symbolic value, attitude towards the products with Islamic symbols, and Muslim consumer" purchase intention has also been ignored in this arena. Some past research have studied the use of religious cues in advertising (Minton, 2020;Hasan et al, 2016;Butt et al, 2018;Naseri and Tamam, 2012;Mallia, 2009;Henley et al 2009) or food packaging (Akbari et al, 2018;Hussin, Yusoff and Yusof, 2015;Bakar et al, 2013) and its impact on Muslim consumers" responses such as purchase intention, while some other studies focused on halal product purchase intentions (Nurhayati, and Hendar, 2019;Naseri, 2021;Ali et al, 2020;Yunus et al, 2014;Shaari and Arifin, 2009;Mukhtar and Butt, 2012;Varinli et al, 2016;Aziz and Chok, 2013); Islamic branding or Islamic Brand purchase intention (Ya et al, 2017;Kusumawardhini, Hati and Daryanti, 2016;Bukhari and Isa, 2019;Alserhan, 2010). None concerns the role of attitude towards the product with Islamic symbols along with religiosity and perceived religious symbolic value in influencing the consumers" purchase decision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Religious beliefs are particularly relevant to understanding consumer behavior (Mathras et al, 2016; Minton, 2016, 2020) because religions are undergirded by texts that are generally agreed upon by followers of a religion (Schmidt et al, 2014). These generally agreed upon texts provide a foundation for similar beliefs that can inform how groups of consumers adhering to the same religion should respond similarly in consumption situations (Agarwala et al, 2019).…”
Section: Religion Belief Congruence Theory and Animal–human Continumentioning
confidence: 99%